Empty fruit bunch (EFB) fibers as reinforcement in polypropylene - Nuramirah, Che Lah; Noor Mazni, Ismail (Penerbit UMP, 2019)
In this work, EFB fibers / Polypropylene matrix were prepared using hot pressing tool at 3 different ratio (5%, 10%, and 15% EFB/PP). Tensile test and impact test were done according to ASTM standard, ASTM D638 and ASTM D256, respectively. The results from tensile test and impact test showed that the prepared specimens of EFB/PP composite have slightly higher elastic modulus (1.95 GPa - 2.1 GPa) compared to pure PP (1.91 GPa) but at the same time they are lack of ductility and have low impact strength, at a range of 4.6 kJ/m2 to 5.5 kJ/m2 compared to pure polypropylene with impact strength value of 18.18 kJ/m2. From the fractured surface analysis, the initial micro cracks were seen mostly occurred at the interface of the EFB/PP and air voids which act as a crack propagation site.